Steel sliding-controlled coupled beam modules: Development and seismic behavior for a moment resisting frame. (15th September 2015) - Lin, Ying-Cheng
Highlights: An innovative steel sliding-controlled coupled beam (SC-CB) modular unit is proposed. Relative sliding mechanism enables compatibility with existing secondary structures. Closed-form solutions to SC-CB internal forces and connection moment are developed. SC-CBs lower peak story drifts and eliminate residual drifts for steel buildings. SC-CBs reduce floor acceleration and story drifts; thus mitigate seismic damage. Abstract: This paper presents a steel sliding-controlled coupled beam (SC-CB) module that employs relative sliding mechanism combined with contributions of built-in-unit post-tensioning (PT) steel and supplemental energy-dissipating devices. Member internal bending moment, axial and shear forces, total PT force, and SC-CB-to-column connection moment of an SC-CB module were developed and compared with nonlinear analysis results. A prototype building was designed, and static pushover and dynamic time history analyses were performed to study the limit states and seismic response under design basis earthquakes and maximum considered earthquakes. Analysis results showed that developed equations are adequate for calculating module response as subjected to lateral loads. Time history analysis statistic results indicated SC-CB modules offer steel moment frame building systems with the potential of: (1) superior damage-free moment resistance and eliminating residual drifts; (2) resolving deformation incompatibility concerns with secondary structures of self-centering steel moment frames due to large story drifts and beam–column-connection rocking mechanism; (3) cost-effectively advanced damage-inhibition seismic response.